RANCANG BANGUN SISTEM INFORMASI PENJUALAN PAKAIAN BERBASIS WEB PADA DISTRO CHANNEL CIREBON DENGAN METODE CRM OPERASIONAL (STUDI KASUS : DISTRO CHANNEL) - cecep juliansyah abbas; ucup sopyan; dadan nugraha (FKOM UNIKU, 2020)
Distro Channel is located on Jalan Raya Letjend S Parman, Pabuaran Cirebon. At this time, Distro Channel only markets its products around Pabuaran. Efforts to get new entrants depend on the participation of old customers to spread information about the Distro Channel to other prospective customers. This becomes less effective in terms of time and it can result in a greater risk of losing customers. This study aims to create an information system that implements operational CRM methods so that customers can make product purchases as desired by accessing the Distro Channel website. This research uses the waterfall system development method. The stages of this waterfall are analyzing system requirements, making system design, implementing system, testing and operating and maintaining system. The implementation of CRM that is applied in the Distro Channel, namely giving points in accordance with the provisions will get 1 point for multiples of spending Rp. 65,000, - points with a certain amount can be exchanged with the promo product points that have been provided, these points can be used as a discount of Rp. 1,000, -. The application of CRM in this system is expected to be able to improve services so that it impacts on increasing customer loyalty. Keywords: Information Systems, Distribution Channel, operational CRM, Waterfall, Sales Website, customer loyalty, points